PENGARUH DANA PIHAK KETIGA DAN KECUKUPAN MODAL TERHADAP PROFITABILITAS PADA BANK RIAU KEPRI KOTA BATAM - Putra, Dedi Gunawan; Raymond, Raymond (SCIENTIA JOURNAL, 2019)
The purposive of this study to determine the influence of third-party funds and capital adequacy ratio to profitabilitas at Bank Riau Kepri Batam city. The data usedin this research is secondary data such as monthly financial statement Bank Riau Kepri Batam city for a periodof five years from 2012 to 2016. The sample used probability sampling method in which all of the population has a chance to be a sample of 60 observations. The method of analys in this study using multiplelinier regression. The result showed that the partial of third-party funds and significant effect on profitabilitas of 0,000 and capital adequacy ratio significant on profitabilitas of 0,013. Simultaneously, third-party funds and capital adequacy ratio significantly positif on profitabilitas. Rated R Square of 81,0%. this shows the value of variabel third-party funds and capital adequacy ratio are able to explain the profitabilitas amounted to 81,0%.